The Effect of Current Ratio and Debt to Assets Ratio on Debt to Equity Ratio at PT Adhi Karya (Persero) Tbk Which are Listed on the Indonesia Stock Exchange for the Periode 2013-2022 - Siti Ayu Sagita; Dwinanto Priyo Susetyo (Formosa Journal of Social Sciences (FJSS), 2024)
This study aims to analyse how PT Adhi Karya (Persero) Tbk, a company listed on the BEI in Indonesia, is affected by the CR and DAR in relation to its DER. Using a purposive selection strategy, this quantitative study draws 40 samples from financial records covering the years 2013–2022. Classical assumption testing and multiple linear regression analysis are the approaches utilised for data analysis. The F-test and the T-test are then used for hypothesis testing. The study found a medium amount of closeness between the CR and the DER, with a correlation value of -0.672342. A correlation value of 0.976407 between DAR and DER places it in the strong category. An study of the contribution of the independent variables, namely the CR and DAR, yields a DER value of 95.2%, while other factors account for the remaining 4.8%. Since it generates a sig value of 0.0000 < 0.05, the CR value significantly impacts the DER, according to incomplete study. With a sig value of 0.0000 < 0.05, DAR significantly impacts the DER. At the same time, the DER is significantly impacted by the two independent variables, CR and DAR, with a sig value of 0.0000 < 0.05